Adaptasi Semangat Merdeka Belajar dengan Penerapan Model Pembelajaran Project Based Learning Sebagai Bentuk Inovasi dalam Pembelajaran: Indonesia - Fitra Fitra; Sonia Maifa (Journal of Pedagogy and Online Learning, 2022)
The spirit of independent learning is a learning process where teachers and students have the freedom to explore knowledge and skills associated with the environment in order to produce human resources that fit the profile of Pancasila students and can compete in the professional world. The purpose of this study is to convey that the spirit of independent learning can be adapted to the learning process using a project-based learning model. The method used is literatur review with a descriptive qualitative approach. The results of this study are (1) the concept of independent learning includes 4 outlines, namely Minimum Competency Assessment, Character Survey, Expansion of Learning Outcome Assessment, and Equalization of Education Quality. (2) Independent learning includes 4 policies, namely national standard school exams organized by schools, minimum proficiency assessment and character surveys, simplification of learning planning plans, and new student admission zoning system (3) project based learning is considered relevant to be adapted to the spirit of independent learning because it involves student activity and experience in the field. Based on this explanation, this study concluded that the adaptation of the spirit of independent learning with learning project-based learnig models has a positive impact in increasing the activeness, curiosity, and spirit of learning of students.